Analysis High Order Level Thinking Skills of High School Students in Chemistry Learning - Marlina Marlina; Samsul Hadi; Abdul Rahim (Journal of Educational Chemistry (JEC), 2023)
This study aims to describe the high-order thinking skills of high school students. The research method used is a descriptive method with a quantitative approach. The sampling technique used was the random sampling technique. The research subjects were 488 high school students. The data collection technique is a two-tier multiple choice test consisting of twenty questions covering analyzing, evaluating, and creating. Based on the research results and discussion, high-order thinking skills of high school students showed an average in the very high category with a percentage of 1.8% with a frequency of 9 students. The ability of students in the high category has a percentage of 19.9%, with a frequency of 97 students and the ability of students in the medium category is 49%, with a frequency of 239 students. Meanwhile, the average in the low category is 21.9%, with a frequency of 107 students and the ability of students in the very low category has a percentage of 7.4% with a frequency of 36 students. Overall, high-order thinking skills in high school in Tegal are in the medium category.